(untitled) (International Journal of Engineering and Computer Science, 2018)
Automation plays very important role in our lives. It makes the work easier and simpler so for simplified and easy living. Government of India has proposed Digital India campaign. Making this campaign successful involves reducing conventional methods used by small scale industry. Contributing to this campaign we are proposing a solution for business industry to reduce their paper work. The proposed system will provide database management for employee details. Along with this other modules of the system includes prediction algorithm for predicting site details depending on customer needs. The concept of Office Automation system provides advantage of no data duplication, data prediction and easy data backup with a user friendly interface. Overall project is divided into four modules and these modules can be accessed by admin and supervisor. Admin is authorized to log in and add details worker, client, vendor and also allowed to view the database and update the worker details.